Evaluating Impacts of Trophic Interactions on the Effectiveness of Single-Species Fisheries Management - Xing, Lei; Chen, Yong; Li, Bai; Tanaka, Kisei R.; Boenish, Robert; Ren, Yiping; Xu, Binduo (Frontiers in Marine Science, 2021)
Single-species fisheries management (SSFM) is applied to many fisheries ecosystems around the world. The associated ecological impacts are usually not well understood due to the lack of considering trophic interactions among species in the ecosystem. This impedes the implementation of SSFM in an ecosystem context and reduces our ability to understand the possible ecological impacts of fishing activities. This study focuses on two economically important species in the Jiaozhou Bay, China: the short-lived, fast-growing, and relatively abundant Japanese mantis shrimp (Oratosquilla oratoria) and the long-lived, slow-growing, and less abundant Korean rockfish (Sebastes schlegelii). We evaluated how varying trophic interactions influenced O. oratoria and S. schlegelii (i.e., target-species) who were managed under constant fishing pressure. The increase of fishing pressure to other species (i.e., non-target species) was beneficial to O. oratoria and S. schlegelii. O. oratoria was more sensitive to the decrease of fishing pressure to other species. The predation mortality of age-0 O. oratoria increased with the increased fishing pressure to other species. The predation mortality of age-1 O. oratoria and age-0 S. schlegelii had negative relationships with the fishing pressure to other species. Age-1 S. schlegelii seemed not to be sensitive to the changes in trophic interactions. The predation mortality of O. oratoria and S. schlegelii had bigger changes than the starvation mortality after fishing changed. It suggested the prey-predator relationship had a bigger impact than the food competition. The increase of high-trophic-level fish Johnius belangerii fishery positively impacted O. oratoria, but negatively impacted S. schlegelii. S. schlegelii was more sensitive to the changes of the low-trophic-level fish Pholis fangi fishery. Given the complex dynamics of ecosystems, this study highlights the importance of species-specific responses of fishes to shifting trophic interactions in fisheries management.